EFEKTIVITAS PROGRAM KELUARGA HARAPAN DALAM RANGKA PENANGGULANGAN KEMISKINAN DI KECAMATAN RENGASDENGKLOK - Sugiyana, Ratna; Kurniansyah, Dadan; Rizki, Mochamad Faizal (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Asically, poor people are people who are weak in the ability to fulfill their basic needs such as clothing, food and shelter and also do not have the ability to do business because everything they have is so limited that they are unable to participate in a decent social life. One of the special programs issued by the government is the Family Hope Program as an effort to build a social protection system for the poor in order to maintain and improve the social welfare of the poor as well as an effort to break the chain of poverty. In this study, researchers used a descriptive method with a qualitative research approach. The data collection technique is done by literature study, observation, interview, documentation and triangulation. Data is determined from sources based on nonprobability sampling techniques. The informants in this study were 6 informants consisting of Social Service employees as key informants. PKH Coordinator and PKH Facilitator as secondary informants. And the community, especially the community members of the Family Hope Program as informants. This research uses Edy Sutrisno's theory of effectiveness which consists of understanding the program, being on target, on time, achieving goals and real change. The results of this study indicate that the Harapan Family Program has not been running effectively where there are still obstacles in the implementation process.